2022
DOI: 10.1155/2022/1041880
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Authentication Scheme for Digital Rights Management System

Abstract: With the increasing number and popularity of digital content, the management of digital access rights has become an utmost important field. Through digital rights management systems (DRM-S), access to digital contents can be defined and for this, an efficient and secure authentication scheme is required. The DRM authentication schemes can be used to give access or restrict access to digital content. Very recently in 2020, Yu et al. proposed a symmetric hash and xor-based DRM and termed their system to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…This section discusses the efficiency and security attributes of currently available authentication techniques and our proposed protocol for DRM systems. [10][11][12]17,19,20,27 In Tables 3 and 5, we analyze the costs associated with both the execution and the communication respectively of these methods. All of the tables above let us carry out comparative research in the aspect of security and performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This section discusses the efficiency and security attributes of currently available authentication techniques and our proposed protocol for DRM systems. [10][11][12]17,19,20,27 In Tables 3 and 5, we analyze the costs associated with both the execution and the communication respectively of these methods. All of the tables above let us carry out comparative research in the aspect of security and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Hussain et al 20 demonstrated that Yu et al's 12 strategy was insecure and susceptible to privileged insider attacks, user impersonation attacks, and licensing server impersonation attacks while also proposing an improved authentication mechanism for the DRM system. However, Hussain et al stored the sensitive data on the server database and user smartcard.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations